2005
DOI: 10.1111/j.1551-2916.2005.00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Study on PbO–SiO2 Glasses by X‐Ray and Neutron Diffraction and 29Si MAS NMR Measurements

Abstract: Structure of xPbO–(100−x)SiO2 (x=25–89) glasses has been investigated by means of the X‐ray and neutron diffraction and 29Si MAS NMR measurements. In the radial distribution functions of all the glasses, the Pb–O correlation was observed at 0.23 nm, indicating that the PbO3 trigonal pyramids units do exist in the whole glass forming composition range. Furthermore the existence of the first Pb–Pb correlation at ∼0.385 nm in the whole composition range suggests that the basic structural unit is considered to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
44
2
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 20 publications
4
44
2
3
Order By: Relevance
“…In order to understand why this system can form glasses in a very large range of composition by comparison to alkaline earth silicate glass systems [2,3], numerous studies have been reported. The local structures of these compounds have been widely investigated by NMR [4][5][6][7][8], X-ray spectroscopy [8][9][10][11][12][13][14][15][16] and molecular dynamics [16][17][18]. But, even if considerable efforts have been made to explain the composition dependence of the structure and the role played by lead, there is still not a complete consensus on the subject [16,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to understand why this system can form glasses in a very large range of composition by comparison to alkaline earth silicate glass systems [2,3], numerous studies have been reported. The local structures of these compounds have been widely investigated by NMR [4][5][6][7][8], X-ray spectroscopy [8][9][10][11][12][13][14][15][16] and molecular dynamics [16][17][18]. But, even if considerable efforts have been made to explain the composition dependence of the structure and the role played by lead, there is still not a complete consensus on the subject [16,14].…”
Section: Introductionmentioning
confidence: 99%
“…They said also that the connectivity of the silicate network breaks at around 45% of lead content and finally they reported that the lead pyramids form a continuous (mainly edge sharing) network even at relatively low PbO concentrations (>20%). Takaishi et al [8] proposed that, in the whole composition range, the basic structural unit is the Pb 2 O 4 unit, which consists of edge-shared PbO 3 pyramids and that these Pb 2 O 4 units are present in the silicate network even at low PbO content.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed knowledge of the physical properties, particularly electronic, and internal structure of these glasses is critical if they are to be used in all-optical switches. The present study concerns glasses of the lead-silicate family, which have been the subject of several recent experimental and theoretical studies [1][2][3][4][5][6][7][8][9][10][11][12][13]. Previous studies have presented two differing views on the nature of the glass structure as a function of lead concentration.…”
Section: Introductionmentioning
confidence: 99%
“…They added also that the connectivity of the silicate network breaks at around 45% of lead content and finally they reported that the lead pyramids form a continuous (mainly edge sharing) network even at relatively low PbO concentrations (>20%). Takaishi et al [21] proposed that, in the whole composition range, the basic structural unit is the Pb 2 O 4 unit, which consists of edgeshared PbO 3 pyramids and that these Pb 2 O 4 units are present in the silicate network even at low PbO content. Tanaka et al [22] suggested that a detailed comprehension of the glass structures, the nature of the bonding of lead and inhomogeneity still need further studies.…”
Section: Introductionmentioning
confidence: 99%